Bureaucratic Reform in Indonesia: From “Public Administration" to "Public Management" - Basuki Rahmat; Beni Hartanto; Acep Hilman (Journal of Local Government Issues, 2024)
Indonesia has continued to experience increasingly complex, global developments and requires change. However, there has been no reform in the government sector that is needed to anticipate these developments, especially regarding public administration. The aim of this research is to analyze the public administration reform in Indonesia. The research method used is a qualitative research method, and literatures study for gathering the data. The research results show that government institutions no longer monopolize the roles that have previously been the authority of the government. Therefore, the public administration paradigm needs to be reformed starting from government to the governance process. The government needs to increase management capacity and change the culture towards a new public management direction. In the systems paradigm, the government is encouraged not to focus on systems and procedures, but to be more performance oriented and work by emphasizing an entrepreneurial spirit.